Nieprzemijające znaczenie herbartowskiej koncepcji nauczania - Benner, Dietrich (Horyzonty Wychowania, 2017)
Educational teaching is an inventive idea of combining upbringing and education, which was ﬁ rst developed by Johann Friedrich Herbart, a 19th-century German philosopher and pedagogue. He presented it as one of the three stages of the spiritual and intellectual development of a pupil (apart from “ruling the children” and management). Herbart’s concept spread soon and found application primarily in the European educational system in the period of the so-called Herbartianism – since 1850s until 1920s. Also in our times the need for upbringing at school is being discussed, though not in the context of Herbart. Dietrich Benner does not aim at coming back to history, but reading of the Herbartian idea in the light of modern didactics.